Exploring the validity of the Fantastic Lifestyle Checklist in an inner city population of people presenting with suicidal behaviours. (February 2016) - Wilhelm, Kay; Handley, Tonelle; Reddy, Prasuna
Purpose: Although patients demonstrate a range of problematic health-related lifestyle behaviours preceding suicidal behaviour, there is little research that routinely measure these behaviours. This paper seeks to establish the utility of health-related lifestyle measure (Fantastic Lifestyle Checklist) in people presenting to a major inner city Emergency Department with a range of suicidal behaviours. Methods: From 2007–2014, data from the 366 patients who had completed the Fantastic Lifestyle Checklist, after referral by the Emergency Department to a service for people with deliberate self-harm or suicidal ideation, were included in the analysis study. A Maximum Likelihood factor analysis was performed to assess the factor structure of the Fantastic Lifestyle Checklist and the resultant factors were explored in relation to measures of health; namely the Depression, Anxiety and Stress Scale and the 12-item Short-Form Health Survey. Results: A three-component factor structure emerged comprising Component 1 ' positive life investments', Component 2 'poor emotional regulation' and Component 3 'poor health behaviours'. There was a significant negative correlation between 'positive life investments' and each of the Depression, Anxiety and Stress scales subscales and significant positive associations with 'poor emotional regulation' and Short Form Health Survey-12 mental health scores. Only the Short Form Health Survey-12 physical health subscale was weakly correlated with 'poor health behaviours', in females. Conclusion: Our findings support the construct and concurrent validity of the Fantastic Lifestyle Checklist measure. The three factors obtained for the Fantastic Lifestyle Checklist were coherent and seem useful for research and clinical practice.